General and Local Morphological Anomalies in Amblyomma lepidum (Acari: Ixodidae) and Rhipicephalus decoloratus Infesting Cattle in Uganda. Issue 3 (21st December 2018) - Balinandi, Stephen; Mugisha, Lawrence; Bbira, Johnson; Kabasa, William; Nakayiki, Teddy; Bakkes, Deon K; Lutwama, Julius J; Chitimia-Dobler, Lidia; Malmberg, Maja
Abstract: Morphological abnormalities in ticks seem to be rare phenomena in nature, and are underreported in Africa. In this article, we describe general and local anomalies in two Amblyomma lepidum females and one Rhipicephalus decoloratus female collected from cattle in Moroto and Kasese districts, Uganda. One A. lepidum specimen displayed metagynander gynandromorphism with the presence of both male and female features in the same organism. The second A. lepidum female showed slight asymmetry and lacked a genital aperture. The R. decoloratus displayed multiple anomalies that included asymmetry on the right side in association with ectromely, chitinous formations and constrictions on the left side. This article presents the first report of metagynander gynandromorphism, as well as genital aperture absence which is not linked to gynandromorphism, in A. lepidum collected from cattle.